Artificial Intelligence in Classroom Learning: Building Students’ Growth Mindset and Critical Thinking in the Age of AI - Srikusuma, Mar’atul Khusna; Noorfriska, Salsabilla; Nurhikmah, Ulfach Oktaviani; Kusumaningtyas, Dian Artha (The Indonesian Institute of Science and Technology Research, 2026)
The rapid advancement of artificial intelligence (AI) technologies has significantly influenced contemporary educational practices worldwide. Generative AI tools are increasingly accessible to students and can instantly provide explanations, summaries, problem-solving assistance, and complete written responses. Although these technologies offer important opportunities for improving access to information and supporting learning efficiency, they also create challenges related to students’ cognitive engagement, analytical ability, and critical thinking development. Many educators are concerned that students may rely excessively on AI-generated outputs and gradually reduce their independent intellectual effort. This study aims to examine the role of AI in classroom learning and explore how the concept of growth mindset can support responsible and reflective AI usage in educational contexts. The research employs a qualitative literature review and conceptual analysis of recent academic studies and classroom practices related to AI integration in education. The findings indicate that students require clear guidance regarding the strengths and limitations of AI systems. AI should be positioned as a cognitive support tool rather than a replacement for human reasoning and problem-solving processes. The study also highlights that AI systems may generate inaccurate or contextually inappropriate responses, emphasizing the importance of critical evaluation. A practical example involving AI recommendations for short-distance travel demonstrates how AI may fail to fully understand situational context despite producing logically structured responses. Based on these findings, the study proposes a conceptual framework integrating AI literacy, growth mindset orientation, critical evaluation, and reflective learning practices.